The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1144/sp317.15
|View full text |Cite
|
Sign up to set email alerts
|

Geology at the crossroads: aspects of the geological career of Dr John MacCulloch

Abstract: Dr John MacCulloch MD was a pioneer of geological cartography. Prior to his surveys there had been few attempts to map and survey Scotland. Of these few, only the student efforts of Louis-Albert Necker de Saussure and the published map of Aimé Boué have attempted to show the whole country. MacCulloch's geological map of Scotland, published posthumously in 1836, remains one of the great cartographic milestones in the history of geology. Earlier, MacCulloch was the first government-appointed geologist through hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…The Schiehallion experiment turned out, however, to play a crucial role in the production of MacCulloch's landmark geological map of Scotland (Bowden 2009 Rose & Rosenbaum 1988), and subsequently he was tasked with seeking alternative sites at which the Schiehallion experiment could be repeated, in line with Playfair's suggestion. An appropriate site had to display suitable form (a conical or ridged mountain) with suitable isolation and simple subsurface density distribution.…”
Section: Macculloch's Geological Mapmentioning
confidence: 99%
See 2 more Smart Citations
“…The Schiehallion experiment turned out, however, to play a crucial role in the production of MacCulloch's landmark geological map of Scotland (Bowden 2009 Rose & Rosenbaum 1988), and subsequently he was tasked with seeking alternative sites at which the Schiehallion experiment could be repeated, in line with Playfair's suggestion. An appropriate site had to display suitable form (a conical or ridged mountain) with suitable isolation and simple subsurface density distribution.…”
Section: Macculloch's Geological Mapmentioning
confidence: 99%
“…by such as are competent judges of the real errors and deficiencies'. Bowden (2007Bowden ( , 2009 argues that this sentiment is rather harsh, 10 but one such judge was George Bellas Greenough (1778-1855), the first President of the Geological Society of London, who noted that Playfair observed that lithology appeared to exert control on the form of Schiehallion , the hard, homogeneous quartzite defining Figure 4 from superimposed to indicate extent of Barrow's survey data and Hutton's 1778 modelling (Fig. 4).…”
Section: If the Form And Situation Of The Mountain [Schiehallion]mentioning
confidence: 99%
See 1 more Smart Citation
“…Not far away is his bust. MacCulloch was an early member of the Society, but, unlike Greenough's, his map was not a product of the Society's efforts (Bowden 2009). Like Greenough's map, however, MacCulloch's also conceals a contemporary dispute, this time about the uses of public money (Cumming 1985).…”
Section: The Society Exhibitedmentioning
confidence: 99%
“…The explorer and surveyor, (Sir) Thomas Mitchell really set the ball rolling in 1835 (Mitchell 1838) on his expedition into northwestern New South Wales. It was perhaps appropriate that the first such name he bestowed was that of the energetic Dr John MacCulloch (1773-1835) (on 24 June 1835), President (1816-1818) and producer of a fine map of Scotland, who joined the Society in 1808 (Bowden 2009 (Feeken et al 1970).…”
Section: Economic Interestsmentioning
confidence: 99%